Botulinum toxin in modern clinical and aesthetic medicine: history, applications, risks and future perspectives - Gabriela Kehayova; Stela Dragomanova; Simeonka Dimitrova (Pharmacia)
Botulinum toxin, a potent neurotoxin produced by Clostridium botulinum, has widespread applications in both medical and aesthetic practices due to its ability to inhibit neuromuscular transmission. In clinical medicine, it is used to treat various conditions such as chronic migraines, spasticity, and hyperhidrosis. In aesthetic medicine, it is primarily employed for wrinkle reduction and facial rejuvenation, providing significant efficacy with minimal recovery time. Despite its established therapeutic benefits, improper administration of botulinum toxin can lead to serious adverse effects, including muscle weakness, respiratory compromise, and localised reactions. Therefore, it is essential to ensure precise dosing, skilled injection techniques, and appropriate patient selection to maximise therapeutic outcomes while minimising risks. As the use of botulinum toxin continues to expand in both medical and cosmetic settings, there is a critical need for enhanced safety protocols and stringent regulation to ensure its safe and effective application.